CONTEMPORARY ISSUES ON ASEAN LIBERALIZATION OF LEGAL SERVICE FROM INDONESIA PERSPECTIVE - Nico Hanna Lumanauw, Erick Risky (Transnational Business Law Journal, 2020)
Kuala Lumpur meeting in 1997 has established and concepted three pillars in ASEAN known as ASEAN Economic Community (AEC), ASEAN Security Community (ASC), and ASEAN Socio-Cultural Community (ASCC). AEC has been established based on ASEAN Economic Blueprint 2015, to reach the target of ASEAN Vision 2020 targets, ASEAN member states made several cooperation agreements such as Preferential Trade Agreement (PTA), ASEAN Free Trade Area (AFTA), ASEAN Framework Agreement on Services (AFAS), ASEAN Investment Area (AIA 1998), and etc. Related to AEC nowadays, massive investment occurred in the ASEAN region, economic growth reached 5% in this region. There's various kinds of bussiness development of the services sector, mainly in legal service, in facing globalization and liberalization of business movement after Free Trade Agreement comes into force in ASEAN. The differences of the governmental system, geographical condition, and the divergence of jurisdiction also reflecting in the ASEAN Countries to regulate each national law regulation. This paper explain the comparison existing ten ASEAN countries national legislation, government decree relating to the liberalization of national legal services in each country. This research was expecting to help Indonesian government re-evaluate the Authorities and regulation related in modern business sector development, in result from the demand of capable attorneys by endorsing foreign lawyers to get practices in Indonesia to transfer knowledge to local attorneys.